Highly Active [Pd(μ‐Cl)Cl(NHC)]2 Complexes in the Mizoroki–Heck Reaction. Issue 12 (18th March 2013) - Tessin, Ulrike I.; Bantreil, Xavier; Songis, Olivier; Cazin, Catherine S. J.
Abstract: A series of Pd dimers bearing an N‐heterocyclic carbene ligand was studied in the Mizoroki–Heck reaction. [Pd(μ‐Cl)Cl(SIPr)]2 (SIPr = { N, N′ ‐bis[2, 6‐(diisopropyl)phenyl]imidazolidin‐2‐ylidene}) was shown to be highly efficient in this cross‐coupling for a range of aryl and heterocyclic bromides, with low palladium loading (20–200 ppm). Abstract : Commercially available [Pd(μ‐Cl)Cl(SIPr)]2 (1 ) is a highly efficient catalyst for the Mizoroki–Heck reaction, requiring ppm levels of palladium catalyst.